Mongolia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Mongolia's macroeconomic performance in 2005-06 has been robust, underpinned by a run-up on copper and gold prices, declining inflation, and budget and external current account surpluses. Real GDP growth in 2005-06 is estimated at 7 percent, in line with the average pace since 2002. The mineral sector has been a key engine of growth, supported by favorable weather conditions, and buoyant recovery in the construction and services sectors. Mongolia's medium-term outlook for sustained growth and poverty reduction is broadly favorable, but subject to risks.